2021
DOI: 10.3389/fpubh.2020.596332
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Prevention During Work Resumption: A Case Study of One Chinese Company's Experience

Abstract: Background: The COVID-19 epidemic not only brings challenges to the health of people all over the world, but also impacts the global economy, and employment. Therefore, promoting industry and business to resume work safely has become an important step to be taken by all countries in overcoming the economic recession and restarting growth.Objective: This study aims to elaborate on epidemic prevention measures a Chinese company (Company C) took during work resumption.Methods: In this study, we used a case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…From April 10 to April 24, 2020, telephone interviews were conducted to investigate the experiences and perceptions of Chinese university students toward the COVID-19 pandemic ( 18 ). This study provided detailed descriptions of experience and perceptions of Chinese university students regarding the COVID-19 pandemic by comparing the similarities and differences between coded data ( 19 22 ). An inductive approach was chosen for presenting original, first-hand, qualitative information on experience and perceptions of Chinese university students regarding the COVID-19 pandemic ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…From April 10 to April 24, 2020, telephone interviews were conducted to investigate the experiences and perceptions of Chinese university students toward the COVID-19 pandemic ( 18 ). This study provided detailed descriptions of experience and perceptions of Chinese university students regarding the COVID-19 pandemic by comparing the similarities and differences between coded data ( 19 22 ). An inductive approach was chosen for presenting original, first-hand, qualitative information on experience and perceptions of Chinese university students regarding the COVID-19 pandemic ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the main themes were created and described. The authors of this study independently returned to the raw interview data, determined what themes were identified from the data and then compared and contrasted all the themes until consensus was reached in order to ensure consistency in coding 30 and establish trustworthiness.…”
Section: Methodsmentioning
confidence: 99%
“…The timing for the resumption of work and its impact on the risk of a secondary outbreak can be estimated (Wang, Tang, et al., 2020 ). The work resumption strategies were evaluated and the corresponding risk assessments can be provided for decision‐making (Bai et al, 2020 ; Zhang, Ge, et al., 2021 ; Zhang, Wu, Li, & Li, 2021 ). There is evidence that various resumption strategies might have different potential to control the outbreaks amid society reopening (Ge et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The timing for the resumption of work and its impact on the risk of a secondary outbreak can be estimated (Wang, Tang, et al, 2020). The work resumption strategies were evaluated and the corresponding risk assessments can be provided for decision-making (Bai et al, 2020;Zhang, Ge, et al, 2021;Zhang, Wu, Li, & Li, 2021).…”
Section: Introductionmentioning
confidence: 99%